In situ application of alternate potentials with chlorination synergistically enhanced biofouling control of titanium condenser materials. (October 2019) - Anandkumar, B.; George, R.P.; Rao, Ch Jagadeeswara; Philip, John
Abstract: Titanium with excellent corrosion resistance when used as the condenser material undergoes severe biofouling problems due to its enhanced biocompatibility. Power plants employ various conventional biofouling treatment strategies involving chlorination and mechanical cleaning. The main objective of this work was to supplement the existing conventional biofouling control technique; chlorination with in situ application of potential on Ti material to enhance cleanliness of the condenser system. The alternate potentials were applied in the following pattern: (cathodic potential of −600 mV (Ag/AgCl) for 15 min; anodic potential of +600 mV for 15 min as one cycle and the cycle was repeated once again). Ti specimens were treated with conventional chlorination method alone and in combination with the applied potential. The specimens were withdrawn after a week and the biofouling control efficacy was analyzed using advanced microscopic and electrochemical techniques. Two orders of reduction in the bacterial density were observed under the individual influence of both the applied potentials and chlorination. Finally three order reduction of bacterial density was achieved during the combined treatment of applied potentials and chlorination. The results demonstrated that use of alternate potential alone controlled biofilm formation better than chlorination, while the combined treatment of alternate potential with chlorination synergistically showed superior control of biofouling. Graphical abstract: Image 1 Highlights: Synergistic effect of alternating potentials and chlorination in biofilm control. Titanium specimens exposed to seawater and freshwater for one week. Alternate potentials (−600 mV and +600 mV) applied to Ti in 24 h intervals. Two to three orders of magnitude decrease in bacterial counts in the treated Ti. Microscopic and EIS analysis confirmed the biofouling control by potentials.